Efeitos da substituição da coleta em latões pela coleta a granel na estrutura de captação do leite - Fonseca, Ariângelo Geraldo Nunes da (2004)
The deregulation and trade liberalization in the begin of the 1990 s created the need of competitive strategies in the domestic dairy industry, notably in Mercosul. The new environment imposed a number of changes in this sector, as far as producers and industries are concerned. This dissertation aims to evaluate the result of one of these changes that were implemented in order to gain competitive advantage, by way of quality differentiation or cost savings in logistics. It is a case study about the bulk collection of refrigerated milk at Nestlé Brasil Ltda, which is a very representative firm of the dairy industry and where, until 1995, milk was collected in gallons. This process could be implemented with the introduction of cooling equipments in farms, in a partnership between the industry and producers, and also by the improvement of the industry vehicles used for milk transportation. These investments have produced a number of logistic changes that had a huge impact in the group of suppliers and the whole process of milk purchasing and collection. In this context, this dissertation offers an analysis, from the point of view of supply chain management, focusing on the chain efficiency, and of the New Institutional Economics, focusing on transaction costs.